Respuesta :

Given:

The expression is

[tex]\tan (\cos ^{-1}(-\dfrac{1}{2}))[/tex]

To find:

The value of given expression.

Solution:

We have,

[tex]\tan (\cos ^{-1}(-\dfrac{1}{2}))[/tex]

[tex]=\tan (\pi-\cos^{-1}(\dfrac{1}{2}))[/tex]          [tex][\because \cos^{-1}(-\theta)=\pi -\cos^{-1}\theta][/tex]

[tex]=\tan (\pi-\cos^{-1}(\cos \dfrac{\pi}{3}))[/tex]      [tex][\because \cos \dfrac{\pi}{3}=\dfrac{1}{2}][/tex]

[tex]=\tan (\pi-\dfrac{\pi}{3})[/tex]

[tex]=-\tan (\dfrac{\pi}{3})[/tex]                 [tex][\because \tan(\pi-\theta)=-\tan \theta][/tex]

[tex]=-\sqrt{3}[/tex]         [tex][\because \tan \dfrac{\pi}{3}=\sqrt{3}][/tex]

Therefore, the value of given expression is [tex]-\sqrt{3}[/tex].

ACCESS MORE